Employee Performance Based on Information Technology, Work Stress, and Work Life Balance as an Implementation of SDG's No. 8 at PT PLN Indonesia Power UPB Asam-Asam. - Saleh, Muhammad; Hermawan, Sigit; Sriyono (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
Employee performance plays an important role in organizational success, especially in the energy sector which faces various challenges and changes. Employee performance also plays a crucial role in maintaining smooth operations and meeting national energy needs, especially at PT PLN Indonesia Power UPB Asam-Asam. This study aims to examine the effect of information technology, work stress, and work-life balance on employee performance at PT PLN Indonesia Power UPB Asam-Asam. With a quantitative approach, this study involved 125 respondents selected using the Slovin sampling method from a total population of 181 employees. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression. This research is expected to provide strategic insights to improve employee performance, especially in facing the challenges of a dynamic energy industry.